Скейлiнгова природа фрагментiв мiшенi при взаємодiї 28Si з емульсiєю при енергiї 14.6A ГеВ - Ahmad, M. Ayaz; Rasool, Mir Hashim; Ahmad, Shafiq (Publishing house "Academperiodika", 2018)
An attempt has been made to study the fractal behavior of the experimental data on nuclear fragments obtained from 28Si-Emulsion collisions at 14.6A GeV. The whole analysis is performed by using two different methods, namely the methods of scaled factorial moments (SFMs), Fq; and multifractal moments, Gq: We have found that the present data reflect a multifractal geometry for nuclear fragments along with the Monte Carlo events (simulated events). Finally, some evidences of non-thermal phase transitions and the scaling law nature of SFMs have been studied.